Tubulin inhibitors targeting the colchicine binding site: a perspective of privileged structures - Li, Wenlong; Sun, Honghao; Xu, Shengtao; Zhu, Zheying; Xu, Jinyi (Future Science, 2017)
The vital roles of microtubule in mitosis and cell division make it an attractive target for antitumor therapy. Colchicine binding site of tubulin is one of the most important pockets that have been focused on to design tubulin-destabilizing agents. Over the past few years, a large number of colchicine binding site inhibitors (CBSIs) have been developed inspired by natural products or synthetic origins, and many moieties frequently used in these CBSIs are structurally in common. In this review, we will classify the CBSIs into classical CBSIs and nonclassical CBSIs according to their spatial conformations and binding modes with tubulin, and highlight the privileged structures from these CBSIs in the development of tubulin inhibitors targeting the colchicine binding site.